UPAYA PENINGKATAN LULUSAN SIAP KERJA MELALUI PELATIHAN KREATOR KONTEN BAGI SISWA SMK NEGERI RENGEL, TUBAN (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
In recent years, vocational high school graduates have experienced the highest unemployment rates compared to other educational levels, which contradicts the government’s goal of producing work-ready vocational school graduates. Responding to this issue, the academic community of the Mathematics Department at Universitas Airlangga organized a Community Service (PkM) activity for vocational high school students. The PkM program aims to enhance the students’ competencies in content creation, which can serve as a valuable asset when entering the workforce. The partner for this PkM program is SMK Negeri Rengel, located in Tuban, East Java, which specializes in Multimedia and Visual Communication Design (VCD). Although students have been provided with adequate facilities and infrastructure, and have received relevant vocational training, the absorption of graduates into the workforce has not been optimal. Through this training and mentoring in content creation, it is hoped that students’ competencies will improve, making them better prepared to enter the job market. The training featured guest speakers from the Londo Kampung YouTuber team, who delivered sessions on effective content creation, photography, videography, and editing techniques. The results showed an improvement in student performance, with average test scores increasing from 6.44 (pretest) to 7.05 (posttest). Participant feedback also reflected high satisfaction with the program’s content, speakers, and facilities, yielding an average score of 4.599 out of 5. As a follow-up, students created YouTube content, which was published on the official YouTube channel of the VCD department at SMK Negeri Rengel.   ---   Selama beberapa tahun terakhir, lulusan SMK menjadi lulusan dengan jumlah pengangguran terbesar dibandingkan dengan jenjang pendidikan lainnya. Hal ini bertolakbelakang dengan semangat pemerintah yang mencanangkan program siap kerja untuk lulusan SMK. Menanggapi hal ini, sivitas akademika matematika UNAIR menggelar kegiatan Pengabdian kepada Masyarakat (PkM) untuk siswa SMK. Program PkM yang dilakukan bertujuan untuk meningkatkan kompetensi siswa SMK dalam pembuatan konten sehingga bisa menjadi modal memasuki dunia kerja. Mitra program PKM ini adalah SMK Negeri Rengel, Tuban, Jawa Timur yang memiliki bidang keahlian Multimedia dan Desain Komunikasi Visual (DKV). Meskipun siswa telah difasilitasi dengan sarana dan prasarana yang cukup serta kompetensi keahlian telah disampaikan, namun keterserapan lulusan pada bidang kerja yang ada masih belum maksimal. Melalui kegiatan pelatihan dan pendampingan pembuat konten ini diharapkan dapat meningkatkan kompetensi siswa sehingga lebih siap memasuki dunia kerja. Kegiatan pelatihan menghadirkan narasumber dari tim Youtuber Londo Kampung yang menyampaikan materi terkait pembuatan konten yang efektif, teknik fotografi, videografi dan editing. Hasil pelatihan menunjukkan adanya peningkatan kemampuan siswa ditunjukkan dengan hasil pretest 6,44 dan posttest 7,05. Selain itu, hasil umpan balik menunjukkan kepuasan peserta terhadap pelaksanaan kegiatan, meliputi: materi, narasumber, dan fasilitas dengan nilai rata-rata keseluruhan 4,599 dari skala 1-5. Tindak lanjut dari kegiatan ini berupa penugasan pembuatan konten Youtube yang hasilnya telah diunggah di channel Youtube DKV SMK Negeri Rengel.
Keywords: Content creator; Photography; Videography